High-entropy amorphous layered double hydroxide electrocatalyst as well as preparation method and application thereof
Preparation by the high-entropy amorphous layered double hydroxide electrocatalyst CrCoNiFe-LDH, the problems of low oxygen evolution reaction efficiency and poor structural stability in electrolytic water/sea water were solved, and high efficiency was achieved. Stable electrolytic oxygen evolution reaction.
Patent Information
- Application Number
- CN202411505505.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The existing layered double hydroxide (LDH) catalysts have slow kinetic reactions in electrolytic water/seawater, resulting in low hydrogen production efficiency of electrolytic water/seawater, poor structural stability and susceptible to corrosion.
Using high-entropy amorphous layered double hydroxide electrocatalyst CrCoNiFe-LDH, a single step of deposition on the substrate is formed by electrodeposition method to form a uniformly loaded nanosphere structure, and the multi-component synergy and chromium leaching and re-adsorption mechanism is used to regulate the Structure and active sites of the catalyst.
The structural stability and corrosion resistance of the catalyst are improved, the kinetics of the oxygen evolution reaction are enhanced, and the efficiency and stability of electrolytic oxygen evolution are significantly improved.
Smart Images

Figure CN119392291A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy materials and electrochemical catalysis, and specifically relates to a high-entropy amorphous layered double hydroxide electrocatalyst and a preparation method and application thereof. Background Art
[0002] With the advancement of science and technology, energy demand has been rising. At present, the global energy source is still mainly fossil fuels, which account for more than 83.1% of the energy structure. The proportion of renewable energy such as solar energy and wind energy is increasing rapidly, but they are developing slowly due to time and space constraints. Hydrogen production through water / seawater electrolysis can well solve the intermittent and difficult storage problems of solar energy and wind energy.
[0003] However, there are problems that restrict the development of hydrogen production by electrolysis of water / seawater. There are two half reactions in the process of electrolysis of water / seawater, oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). In the two half reactions, OER involves a multi-electron transfer process, and the kinetic reaction is slow, which seriously affects the efficiency of hydrogen production by electrolysis of water / seawater. In the OER process, a four-electron proton coupling reaction occurs, and four protons are separated from two water molecules to form an oxygen molecule. A large overpotential is required to effectively promote the reaction.
[0004] Layered double hydroxide (LDH) structured materials are considered to be a promising oxygen evolution catalyst due to their abundant reserves, flexible adjustability, excellent electrocatalytic activity for water decomposition, and the fact that LDH materials are prone to dynamic surface reconstruction in alkaline media. However, the low conductivity, limited active sites, poor structural stability, and susceptibility to corrosion by chloride ions and hypochlorite ions, the product of the chlorine evolution reaction, of LDH structured catalysts have become bottlenecks for their widespread application in water / seawater electrolysis. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a high entropy amorphous layered double hydroxide electrocatalyst and a preparation method and application thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a method for preparing a high entropy amorphous layered double hydroxide electrocatalyst, comprising the following steps:
[0008] Chromium nitrate, cobalt nitrate, nickel nitrate, iron nitrate and potassium nitrate are dissolved in water to prepare an electrodeposition solution; the electrodeposition solution is used to deposit a high entropy amorphous layered double hydroxide electrocatalyst (CrCoNiFe-LDH) on a substrate in one step by means of electrodeposition.
[0009] The intercalation anion of CrCoNiFe-LDH prepared by the present invention is hydroxide (OH - ) and a small amount of NO3 - .
[0010] The amorphization in the CrCoNiFe-LDH provided by the present invention can increase the active sites of the unsaturated structure with long-range disorder but medium- and short-range ordered structure. The high entropy strategy composed of multiple components in CrCoNiFe-LDH effectively regulates the d-band center and promotes the reaction kinetics. CrCoNiFe-LDH with more active sites shows higher activity than crystalline catalysts.
[0011] The present invention combines a high entropy amorphous structure with a layered double hydroxide structure, providing a regulation strategy with the best prospects for efficient bifunctional water electrolysis catalysts.
[0012] Preferably, the molar ratio of chromium nitrate, cobalt nitrate, nickel nitrate and iron nitrate is 1:1:1:1.
[0013] Preferably, the molar ratio of chromium nitrate, cobalt nitrate, nickel nitrate, iron nitrate and potassium nitrate is 1:1:1:1:1.
[0014] The role of potassium nitrate in the present invention is to regulate the morphology of the catalyst, and the K element does not exist in the final catalyst.
[0015] Preferably, the deposition voltage of the electrodeposition is -1.0 V vs. SCE, and the total electrodeposition time is 1800 s.
[0016] Preferably, the substrate is nickel foam (NF); in the electrodeposition, the working electrode is nickel foam, the counter electrode is a platinum sheet, and the reference electrode is saturated calomel.
[0017] The second technical solution of the present invention is to provide a high entropy amorphous layered double hydroxide electrocatalyst prepared according to the above-mentioned preparation method of the high entropy amorphous layered double hydroxide electrocatalyst.
[0018] The third technical solution of the present invention is to provide an application of the above-mentioned high entropy amorphous layered double hydroxide electrocatalyst in the preparation of water electrolysis oxygen evolution catalyst.
[0019] The beneficial technical effects of the present invention are as follows:
[0020] The present invention provides a method for preparing a high-entropy amorphous layered double hydroxide electrocatalyst, and the prepared CrCoNiFe-LDH is a nanosphere structure uniformly loaded on a substrate. The excellent catalytic performance of CrCoNiFe-LDH is attributed to the following aspects: 1) the multi-component synergy in the catalyst stabilizes the structure of the catalyst and makes the catalyst structure stable; 2) the chromium element will be leached out during the use of CrCoNiFe-LDH, which promotes the reconstruction of the catalyst and provides abundant active sites, thereby improving the inherent catalytic activity; 3) the chromium element leached out during the use of CrCoNiFe-LDH will be adsorbed on the surface of the catalyst to form an electrostatic layer, repelling chloride ions, thereby improving the corrosion resistance of the catalyst.
[0021] The preparation method provided by the present invention is to obtain a high entropy amorphous layered double hydroxide catalyst by one-step deposition on a substrate, which has the advantages of being simple, rapid, efficient and low-cost. It broadens the selection range of designing low-cost, high-performance electrocatalysts. The preparation method provided by the present invention has a simple process, does not require complicated equipment and experimental steps, and is convenient for large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD patterns of CrCoNiFe-LDH, CoNiFe-LDH and NiFe-LDH prepared in Examples 1 to 3.
[0023] Figure 2 The SEM images of CrCoNiFe-LDH prepared in Example 1; wherein (a) to (d) are SEM images at different magnifications.
[0024] Figure 3 The SEM images of CoNiFe-LDH prepared in Example 2; wherein (a) to (d) are SEM images at different magnifications.
[0025] Figure 4 The SEM images of NiFe-LDH prepared in Example 3; wherein (a) to (d) are SEM images at different magnifications.
[0026] Figure 5 This is the EDS element mapping image of the cations in CrCoNiFe-LDH prepared in Example 1.
[0027] Figure 6 High-resolution transmission electron microscope image and electron diffraction image of CrCoNiFe-LDH prepared in Example 1; wherein (a) and (b) are transmission electron microscope images of different resolutions; and (c) is an electron diffraction image.
[0028] Figure 7LSV curves of CrCoNiFe-LDH, CoNiFe-LDH, NiFe-LDH and NF substrate prepared in Examples 1 to 3.
[0029] Figure 8 The results of the water electrolysis and oxygen evolution stability test of the CrCoNiFe-LDH prepared in Example 1 and the LSV curves of the CrCoNiFe-LDH before and after the cycle.
[0030] Fig. 9 The results of the water electrolysis and oxygen evolution stability test of the CoNiFe-LDH prepared in Example 2 and the LSV curves of the CoNiFe-LDH before and after cycling.
[0031] Fig.10 This is the chromium content curve of the CrCoNiFe-LDH prepared in Example 1 during the CV activation process (0.075V~0.875V vs.Hg / HgO) with different numbers of KOH test solutions.
[0032] Fig.11 It is a line graph showing the chromium content in the KOH test solution at different cycles during the CV activation process (0.075V-0.875V vs. Hg / HgO) of the CrCoNiFe-LDH prepared in Example 1.
[0033] Fig.12 Raman spectra of CrCoNiFe-LDH, CoNiFe-LDH and NiFe-LDH prepared in Examples 1 to 3. DETAILED DESCRIPTION
[0034] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0035] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0036] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0037] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0038] Example 1
[0039] Preparation of nickel foam supported high entropy amorphous layered double hydroxide CrCoNiFe electrocatalyst (CrCoNiFe-LDH):
[0040] (1) Pretreatment of nickel foam: The pretreated nickel foam (thickness 1.0 mm) was cut into 1×2 cm 2 , and then ultrasonically cleaned in the order of acetone, deionized water, hydrochloric acid and alcohol for 30 min, and the cleaned nickel foam was dried at 60 ° C for 6 h;
[0041] (2) Preparation of electrodeposition solution: Dissolve 0.5 mmol of Co(NO3)2·6H2O, 0.5 mmol of Cr(NO3)3·9H2O, 0.5 mmol of Ni(NO3)3·2H2O, 0.5 mmol of Fe(NO3)3·9H2O and 0.5 mmol of KNO3 in 100 mL of deionized water, mix them evenly under the action of ultrasound to obtain an electrodeposition solution.
[0042] (3) Electrodeposition: The pretreated nickel foam was used as the working electrode, the platinum sheet was used as the counter electrode, and the saturated calomel was used as the reference electrode. The prepared electrodeposition solution was placed in an electrolytic cell with a built-in rotor. The rotor was maintained at 300 rpm by a magnetic stirrer and the temperature was kept at room temperature. The electrochemical workstation was operated in the controlled voltage electrodeposition mode with a deposition voltage of -1.0 V vs. SCE and a total deposition time of 1800 s. The prepared samples were rinsed with deionized water and ethanol, respectively, and dried at 60°C for 2 h.
[0043] Example 2
[0044] Preparation of nickel foam supported amorphous layered double hydroxide CoNiFe electrocatalyst (CoNiFe-LDH):
[0045] (1) Pretreatment of nickel foam: The pretreated nickel foam (thickness 1.0 mm) was cut into 1×2 cm 2 , and then ultrasonically cleaned in the order of acetone, deionized water, hydrochloric acid and alcohol for 30 min, and the cleaned nickel foam was dried at 60 ° C for 6 h;
[0046] (2) Preparation of electrodeposition solution: Dissolve 0.5 mmol of Co(NO3)2·6H2O, 0.5 mmol of Ni(NO3)3·2H2O, 0.5 mmol of Fe(NO3)3·9H2O and 0.5 mmol of KNO3 in 100 mL of water, mix them evenly under the action of ultrasound to obtain an electrodeposition solution.
[0047] (3) Electrodeposition: The pretreated nickel foam was used as the working electrode, the platinum sheet was used as the counter electrode, and the saturated calomel was used as the reference electrode. The prepared electrodeposition solution was placed in an electrolytic cell with a built-in rotor. The rotor was maintained at 300 rpm by a magnetic stirrer and the temperature was kept at room temperature. The electrochemical workstation was operated in the controlled voltage electrodeposition mode with a deposition voltage of -1.0 V vs. SCE and a total deposition time of 1800 s. The prepared samples were rinsed with deionized water and ethanol, respectively, and dried at 60°C for 2 h.
[0048] Example 3
[0049] Preparation of nickel foam supported amorphous layered double hydroxide NiFe electrocatalyst (NiFe-LDH):
[0050] (1) Pretreatment of nickel foam: The pretreated nickel foam (thickness 1.0 mm) was cut into 1×2 cm 2 , and then ultrasonically cleaned in the order of acetone, deionized water, hydrochloric acid and alcohol for 30 min, and the cleaned nickel foam was dried at 60 ° C for 6 h;
[0051] (2) Preparation of electrodeposition solution: 0.5 mmol of Ni(NO3)3·2H2O, 0.5 mmol of Fe(NO3)3·9H2O and 0.5 mmol of KNO3 were dissolved in 100 mL of water and mixed evenly under the action of ultrasound to obtain an electrodeposition solution.
[0052] (3) Electrodeposition: The pretreated nickel foam was used as the working electrode, the platinum sheet was used as the counter electrode, and the saturated calomel was used as the reference electrode. The prepared electrodeposition solution was placed in an electrolytic cell with a built-in rotor. The rotor was maintained at 300 rpm by a magnetic stirrer and the temperature was kept at room temperature. The electrochemical workstation was operated in the controlled voltage electrodeposition mode with a deposition voltage of -1.0 V vs. SCE and a total deposition time of 1800 s. The prepared samples were rinsed with deionized water and ethanol, respectively, and dried at 60°C for 2 h.
[0053] The XPS element contents (at.%) of the catalysts prepared in Examples 1 to 3 are shown in Table 1.
[0054] Table 1
[0055]
[0056] The XRD patterns of CrCoNiFe-LDH, CoNiFe-LDH and NiFe-LDH prepared in Examples 1 to 3 are shown in Figure 1 .
[0057] Figure 1 Among them, the curves of CrCoNiFe-LDH, CoNiFe-LDH and NiFe-LDH show amorphous structures.
[0058] The SEM image of CrCoNiFe-LDH prepared in Example 1 is shown in Figure 2 ; Among them, (a)~(d) are SEM images at different magnifications.
[0059] Figure 2 It is shown that the morphology of CrCoNiFe-LDH is nanospheres, which are stacked in the form of nanospheres on the NF substrate, exposing more active sites and giving the material faster transmission efficiency.
[0060] The SEM image of CoNiFe-LDH prepared in Example 2 is shown in Figure 3 ; Among them, (a)~(d) are SEM images at different magnifications.
[0061] Figure 3 It is shown that the morphology of CoNiFe-LDH is nanosheets, which are relatively small and smooth, resulting in a relatively small specific surface area and low intrinsic activity.
[0062] The SEM image of NiFe-LDH prepared in Example 3 is shown in Figure 4 ; Among them, (a)~(d) are SEM images at different magnifications.
[0063] Figure 4 It is shown that the morphology of NiFe-LDH is extremely smooth nanosheets with small size, which also leads to lower intrinsic activity.
[0064] The EDS element mapping image of the cations in the CrCoNiFe-LDH prepared in Example 1 is shown in Figure 5 .
[0065] Figure 5 It shows that the cations Fe, Ni, Co, and Cr in CrCoNiFe-LDH can be evenly present on the surface of the electrocatalyst, proving the success of electrodeposition preparation of the catalyst.
[0066] The high-resolution transmission electron microscope image and electron diffraction image of CrCoNiFe-LDH prepared in Example 1 are shown in Figure 6; Among them, (a) and (b) are transmission electron microscope images with different resolutions; (c) is an electron diffraction image.
[0067] from Figure 6 The nanosphere morphology can be seen in (a) and (b), which is similar to the SEM image. The selected electron diffraction image (c) has no obvious diffraction rings, which corresponds to the XRD result. The amorphous structure can be observed in the high-resolution transmission electron microscope image. This shows that the CrCoNiFe-LDH loaded on the NF is an amorphous structure.
[0068] Electrochemical performance test: When the three electrodes are working, the working electrode is the prepared catalyst, the reference electrode is the Hg / HgO electrode, the counter electrode is the platinum sheet, and the test solution is 1 M KOH solution.
[0069] The LSV curves of CrCoNiFe-LDH, CoNiFe-LDH, NiFe-LDH and NF substrate prepared in Examples 1 to 3 are shown in Figure 7 .
[0070] Figure 7 The test voltage range is 0.075-0.875V vs.Hg / HgO. By comparing the LSV curves, it can be clearly observed that CrCoNiFe-LDH has the best oxygen evolution performance, indicating that after chromium leaching and re-adsorption promotes catalyst reconstruction, it is also beneficial to improve the intrinsic activity of the catalyst for oxygen evolution.
[0071] The CrCoNiFe-LDH prepared in Example 1 was subjected to an electrolytic water oxygen evolution stability test, and the LSV curves of the CrCoNiFe-LDH before and after the cycle were obtained by linear sweep voltammetry. Figure 8 .
[0072] The CoNiFe-LDH prepared in Example 2 was subjected to an electrolytic water oxygen evolution stability test, and the LSV curves of the CoNiFe-LDH before and after the cycle were obtained by linear sweep voltammetry. Fig. 9 .
[0073] Figure 8 and Fig. 9 Display, at 50mA·cm -2 At a current density of 1.5 %, a chronopotentiometry test was carried out for up to 100 h. The test potential of CrCoNiFe-LDH showed almost no obvious decrease. The LSV curve of CrCoNiFe-LDH changed slightly while the LSV curve of CoNiFe-LDH changed significantly, indicating that CrCoNiFe-LDH has excellent OER durability.
[0074] The chromium content curve of the CrCoNiFe-LDH prepared in Example 1 during CV activation (0.075-0.875V vs.Hg / HgO) at different KOH cycles is shown in Fig.10 .
[0075] UV test of Example 1 CrCoNiFe-LDH prepared in the CV activation (0.075 ~ 0.875V vs.Hg / HgO) process of different cycles of KOH test solution chromium content vertex line graph see Fig.11 .
[0076] Depend on Fig.10 and Fig.11 It can be seen that the content of chromium in the solution increases and decreases, that is, the chromium in the catalyst is leached and then adsorbed.
[0077] The Raman spectra of CrCoNiFe-LDH, CoNiFe-LDH and NiFe-LDH prepared in Examples 1 to 3 are shown in Fig.12 .
[0078] Fig.12 The Raman curves of CrCoNiFe-LDH, CoNiFe-LDH and NiFe-LDH show a peak at 522 cm in CrCoNiFe-LDH. -1 Co(OH)2, 530cm -1 The stretching of Cr-OH in Cr(OH)3, 703 cm -1 The positions are MO, MOM, and OMO (M=Ni / Fe).
[0079] 449 cm-1 in CoNiFe-LDH and NiFe-LDH -1 、528cm -1 Ni(OH)2, 529cm -1 At 522cm -1 The location is Co(OH)2 in CoNiFe-LDH.
[0080] The above experimental results show that the present invention uses a one-step electrodeposition method to prepare high-entropy amorphous CrCoNiFe-LDH uniformly loaded on nickel foam, and the morphology and performance of CrCoNiFe-LDH, CoNiFe-LDH, and NiFe-LDH are characterized. The results show that CrCoNiFe-LDH has the best oxygen evolution performance in water electrolysis, which confirms that the leaching and re-adsorption of chromium elements during the use of CrCoNiFe-LDH helps to improve the intrinsic activity of the catalyst, optimize the intermediate binding energy, and enhance the electron transfer rate.
[0081] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a high entropy amorphous layered double hydroxide electrocatalyst, characterized in that: The following steps are involved: Dissolving chromium nitrate, cobalt nitrate, nickel nitrate, iron nitrate and potassium nitrate in water to prepare an electrodeposition solution; The electroplating solution is used to deposit a high entropy amorphous layered double hydroxide electrocatalyst on a substrate in one step by means of electroplating.
2. The method for preparing a high entropy amorphous layered double hydroxide electrocatalyst according to claim 1, characterized in that: The molar ratio of the chromium nitrate, the cobalt nitrate, the nickel nitrate and the iron nitrate is 1:1:1:
1.
3. The method for preparing a high entropy amorphous layered double hydroxide electrocatalyst according to claim 1, characterized in that: The molar ratio of the chromium nitrate, cobalt nitrate, nickel nitrate, iron nitrate and potassium nitrate is 1:1:1:1:
1.
4. The method for preparing a high entropy amorphous layered double hydroxide electrocatalyst according to claim 1, characterized in that: The deposition voltage of the electrodeposition was -1.0 V vs. SCE, and the total electrodeposition time was 1800 s.
5. The method for preparing a high entropy amorphous layered double hydroxide electrocatalyst according to claim 1, characterized in that: The substrate is nickel foam; the working electrode in the electrodeposition is nickel foam, the counter electrode is a platinum sheet, and the reference electrode is saturated calomel.
6. A high entropy amorphous layered double hydroxide electrocatalyst prepared according to the method for preparing a high entropy amorphous layered double hydroxide electrocatalyst according to any one of claims 1 to 5.
7. Use of the high entropy amorphous layered double hydroxide electrocatalyst according to claim 6 in the preparation of a catalyst for oxygen evolution by water electrolysis.